New Radiocarbon-based assessment Supports the Prominence of Tel Lachish during late Bronze age IB-IIA. Issue 6 (18th November 2019) - Webster, Lyndelle; Streit, Katharina; Dee, Michael; Hajdas, Irka; Höflmayer, Felix
ABSTRACT: This article presents a new suite of radiocarbon ( 14 C) dates for the lower portion of the Late Bronze Age (LBA) sequence of Area S, Tel Lachish. The results show that the lowest levels reached by Ussishkin in the 1980s (S-2 and S-3) date significantly earlier than was previously thought. Level S-3, with its monumental architecture, belongs in the 2nd half of the 15th century BCE, as does the commencement of Level S-2. The laminated deposit of S-2 continues through the first half of the 14th century BCE, coinciding at least in part with the Amarna period. This redating leads to improved agreement between archaeological and textual evidence regarding the presence of a substantial, prominent settlement at Lachish during LB IB-IIA, from the reign of Thutmoses III through the Amarna period.